An Analysis of the Aspirations of Undergraduate Agricultural Students - Arunachalam, R; Shri, K P Sathya; Sasmitha, R (Indian Journal of Extension Education, 2020)
Agricultural students have some plans to settle down in specific career after getting degree. In order to understand the diversified aspirations of the agricultural students, the present study was conducted among the 156 undergraduate students of Agriculture in all the constituent colleges of Tamil Nadu Agricultural University Majority of the respondents stated that completing the B.Sc (Agri) degree programme itself as their major educational aspiration. Around 70 per cent of the respondents aspired to settle themselves in suitable positions in any government departments. Around 40 per cent of the respondents were interested in starting their own farms and also to establish their mushroom production units. Around 50 per cent of the respondents expressed their desire to earn an income of more than Rs. 50,000 to Rs. 1,00,000 per month. Most of the respondents expressed their desire to elevate the socio economic needs of their family.